Introduction to information systems - O'Brien, James A. (ill., 2005)
The text’s focus is on teaching the general business manager how to use and manage the most current IT technologies like the Internet, Intranets, and Extranets for electronic commerce and enterprise collaboration, and how IT contributes to competitive advantage, reengineering business processes, and decision making